2016
DOI: 10.1371/journal.pgen.1005878
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Independent Pro-longevity Function of Triacylglycerol in Yeast

Abstract: Intracellular triacylglycerol (TAG) is a ubiquitous energy storage lipid also involved in lipid homeostasis and signaling. Comparatively, little is known about TAG’s role in other cellular functions. Here we show a pro-longevity function of TAG in the budding yeast Saccharomyces cerevisiae. In yeast strains derived from natural and laboratory environments a correlation between high levels of TAG and longer chronological lifespan was observed. Increased TAG abundance through the deletion of TAG lipases prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 97 publications
5
27
0
Order By: Relevance
“…Our results reveal crucial roles of TAG metabolism in membrane lipid breakdown and fatty acid b-oxidation and uncover the evolutionarily conserved function of TAG in protection against lipotoxicity and ROS-induced oxidative damage in plant model systems. TAG accumulation has also been linked to lifespan extension in yeast (Handee et al, 2016) and Caenorhabditis elegans (Narbonne and Roy, 2009). The finding that disruption of SDP1 increases plant survival rates under dark-induced carbon starvation suggests that the role of intracellular TAG in preserving cell viability is likely to be conserved in plants as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our results reveal crucial roles of TAG metabolism in membrane lipid breakdown and fatty acid b-oxidation and uncover the evolutionarily conserved function of TAG in protection against lipotoxicity and ROS-induced oxidative damage in plant model systems. TAG accumulation has also been linked to lifespan extension in yeast (Handee et al, 2016) and Caenorhabditis elegans (Narbonne and Roy, 2009). The finding that disruption of SDP1 increases plant survival rates under dark-induced carbon starvation suggests that the role of intracellular TAG in preserving cell viability is likely to be conserved in plants as well.…”
Section: Discussionmentioning
confidence: 99%
“…One of these ways of aging delay has been discovered by studies of yeast cultured in a nutrientrich liquid medium initially containing 2% glucose (158,159). Under these so-called non-caloric restriction (non-CR) conditions yeast cells are not limited in the supply of calories (47,160,161).…”
Section: Triacylglycerol Metabolism Is a Longevity Assurance Processmentioning
confidence: 99%
“…After entering stationary (ST) phase, yeast cells cultured under non-CR conditions gradually consume TAGs accumulated in LDs during the preceding L, D and PD phases of growth (161). It has been found that in non-CR yeast 1) single-gene-deletion mutations eliminating the TAG lipases Tgl3 and/or Tgl4 increase TAG concentration and extend CLS; 2) a simultaneous lack of DAG acyltransferases Dga1 and Lro1 in the dga1Δlro1Δ mutant strain decreases TAG concentration and shortens CLS; and 3) the overexpression of the DAG acyltransferase Dga1 rises TAG concentration and prolongs CLS (158). It was therefore concluded that an increase in the abundance of TAGs seen in tgl3Δ, tgl4Δ, tgl3Δtgl4Δ and Dga1 overexpressing cells under non-CR conditions is responsible for the extension of their CLS (158,159).…”
Section: Triacylglycerol Metabolism Is a Longevity Assurance Processmentioning
confidence: 99%
“…Biofuel organism engineering efforts require consideration not only of total lipid accumulation, but also of cell health and growth rate. Continual drain on lipid resources may make senescence an issue, as the balance of triglyceride synthesis has been shown to confer an energy dependence increase in longevity to S. cerevisiae [116]. …”
Section: Discussionmentioning
confidence: 99%